Digital media and artificial intelligence in teaching Bahasa Indonesia: Realities, potentials, and challenges - Sukini Sukini; Sri Budiyono; Wisnu Nugroho Aji; Danang Suseno (Journal of Educational Management and Instruction (JEMIN), 2025)
The ongoing digital transformation presents significant opportunities for language education, yet its pedagogical effectiveness in Bahasa Indonesia instruction remains largely underexplored. While digital media is prevalent in Indonesian classrooms, robust research examining its actual impact on student learning and alignment with pedagogical goals is notably limited. Furthermore, the role of Artificial Intelligence (AI) in Bahasa Indonesia learning is still in its nascent, exploratory stage. This qualitative case study investigates the current use of digital media and the perceived potential of AI in the teaching and learning of Bahasa Indonesia at the secondary school level. Data were collected through semi-structured interviews, classroom observations, and document analysis across five Indonesian high schools. Findings reveal that digital media demonstrably enhances student engagement, fosters creativity, and promotes active participation when intentionally aligned with pedagogical objectives. However, its implementation is significantly hindered by persistent challenges such as digital inequality, insufficient teacher readiness, and shallow instructional integration. While AI is not yet formally integrated into Bahasa Indonesia instruction, both teachers and students expressed cautious optimism regarding its potential, particularly in writing support and adaptive learning pathways. This study concludes that successful digital and AI integration in Bahasa Indonesia education necessitates intentional pedagogical design, comprehensive professional development, and robust ethical safeguards. These insights underscore a critical need for targeted policy support and strategic training initiatives to ensure equitable, effective, and sustainable digital innovation in language education, ultimately addressing the identified research gaps and practical challenges.